What factors influence the transition from safe 4.5 to safe 5.0 in a large-scale financial services organization - Hoeseb, Chris (Department of Information Systems, 2025)
As customer needs evolve and the competitive landscape becomes more challenging for large-scale financial services organizations to meet customer demands and remain competitive. Large-scale financial services organizations must respond quickly to market changes and be agile in product and service delivery. This study investigates the factors influencing the transition from Scaled Agile Framework (SAFe) 4.5 to SAFe 5.0 within a prominent large-scale financial services organization. The study, anchored in the qualitative research paradigms of interpretivism and constructivism, revolves around an in-depth case study, delving into the multifaceted complexities and subtleties associated with transitioning to SAFe 5.0 in a large-scale financial organization setting. Using the Organizational Agility Conceptual Model, the study examined various elements crucial for a successful transition. This model encompassed agility drivers, agile enablers, agile capabilities, and agile practices. Notably, the study identified that SAFe 5.0 competencies that are revolving around customer centricity, namely Agile Product Delivery, Team, and Technical Agility, Continuous Learning Culture, and Lean Portfolio Management, are vital factors that influence the transitioning to SAFe 5.0 across all the themes of the organizational agility conceptual model. Furthermore, organizational factors, including leadership, culture, and technological infrastructure, emerged as significant enablers. The organization's inherent agility capabilities and preparedness for change are critical determinants in effectively managing the transition to SAFe 5.0. The study underscored the challenges encountered in breaking down departmental silos, synchronizing business processes with agile methodologies, and extending agile practices beyond IT-centric domains. These challenges were offset by a noticeable organizational leaning towards adapting agile practices and a commitment to fostering a customer-centric innovation culture in line with SAFe 5.0 competencies. This study substantially contributes to both the academic field and practical aspects of organizational agility and the transition to SAFe 5.0. It equips decision-makers within large-scale financial organizations with a thorough, actionable understanding of the factors influencing agile transitioning. By comprehensively outlining the factors influencing the transition from SAFe 4.5 to SAFe 5.0, the study emerges as an indispensable resource, offering foundational insights for organizational leaders and scholars, focusing on the intricacies of agile transitions in a large-scale financial organization context.